NEUROSPECIFIC ENOLASE IN DIAGNOSTICS FOR PERINATAL DAMAGE TO THE CENTRAL NERVOUS SYSTEM IN PREMATURE INFANTS - E.G. Novopol'tseva; V.A. Vorob'eva; O.B. Ovsyannikova; E.N. Solov'eva; Yu.G. Kuzmichev; L.G. Shipova; O.V. Krylova; I.Yu. Korobkova; T.Yu. Kostareva (Union of pediatricians of Russia, 2010)
Neurospecific enolase is an endoenzyme of the central nervous system (CNS) present in neurons of the brain and peripheral neuraltissue. This is currently the only known general marker of all differentiated neurons. The article illustrates the results of determining this enzyme in premature infants with fetal infections and assessment of their importance as a marker of damage to CNS in this group of children. A high level of neurospecific enolase in children with infectious and inflammatory diseases is not only the marker of damage to blood-brain barrier, but also reflects the nature of damage (hypoxia, intoxication, inflammation). This parameter in premature infants with various pathologies may serve as a degree of perinatal damage severity, and along with other parameters, determine the performed therapy tactics. Key words: neurospecific enolase, marker of CNS damage, perinatal damage, children. (Pediatric Pharmacology. - 2010; 7(3):66-70)